Effects of Non-Cavity-Distorting Intramural Fibroids on IVF Outcomes in Patients With Recurrent IVF Failure: Does Myomectomy Change IVF Outcomes? - Buyuker, Ceyda (LIPPINCOTT WILLIAMS \& WILKINS, 2024)
72nd Annual Clinical and Scientific Meeting of the American-College-of-Obstetricians-and-Gynecologists, San Francisco, CA, MAY 17-19, 2024